2017
DOI: 10.21608/ejss.2017.1528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Treatment of Irrigation Ground water on Soil salinity, Nutrients, Water Productivity and Yield Fruit Trees at Sandy Soil

Abstract: THIS APPLIED experiment was conducted at private farm (160 feddans), sustained of soil and water salinity, at km80 of cairo-alexandria desert road (the green wealth farms). four electromagnetic devise (6 inch) set up on the main sources of ground irrigation. one well for each agriculture sector apricot, peach, flame-seedless grape and thompson seedless grape sectors. these sectors has been irrigated by magnetic treated water (mtw), beginning of december2013, through a drip system.The results indicated that mtw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 6 publications
8
16
0
Order By: Relevance
“…Other studies have shown that magnetic treatment improved the quantity and quality of sunflowers [14]. Irrigation with magnetically-treated water improved the productivity of various crops such as apricot (Prunus armeniaca), peach (Prunus persica), flame seedless grape (Vitis vinifera), and Thompson seedless grape (Vitis vinifera) as compared to those irrigated with untreated water [15].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that magnetic treatment improved the quantity and quality of sunflowers [14]. Irrigation with magnetically-treated water improved the productivity of various crops such as apricot (Prunus armeniaca), peach (Prunus persica), flame seedless grape (Vitis vinifera), and Thompson seedless grape (Vitis vinifera) as compared to those irrigated with untreated water [15].…”
Section: Introductionmentioning
confidence: 99%
“…These results are in harmony with those obtained by, Mohammed et al, (2010) who demonstrated that there are numerous advantages to plant growth resulted from using of natural organic and inorganic products like magnetic iron which improved soil structure, improving water holding capacity and cation exchangeable capacity, and improving crop nutrition from macro and micro nutrients and finally the soil become more energy and vigor. It is worth to mention that the magnetic irrigation gave great impacts on the availability of NPK and micro-nutrients (Fe, Mn, Zn and Cu) all during fertilization season of Apricot, Peach, Flame and Thompson seedless Grape (Fanous et al, 2017).…”
Section: -Olive Fruits Macro and Micro Nutrients Contentmentioning
confidence: 99%
“…Significant response in the soil chemical properties (pH, EC, Na + , Cl -, SAR, available nitrogen, phosphorus and potassium contents) because of irrigation with the magnetized saline water compared to the normal water (Abd-Elrahman and Osama, 2017). Also, irrigation with magnetic treated water considered as a one of valuable modern technologies that improve crop production and alleviate salinity of soil and water (Fanous et al, 2017). Magnetized water technology may refer to technique can improve of both crops yield and save irrigation water .…”
Section: Introductionmentioning
confidence: 99%